Predictors of positive outcomes of a school food provision policy in Australia - Pettigrew, Simone; Donovan, Robert; Jalleh, Geoffrey; pescud, M. (Oxford University Press, 2014)
canteen managers and Parents & Citizens Committee members provided general feedback on the policy and identified various factors that appeared to be related to its successful implementation. In the following quantitative phase of the study, 1200 parents responded to a telephone questionnaire and 310 principals responded to an internet-based questionnaire. The primary outcome variables were, respectively, the extent to which parents reported that their children's diets were healthier as a result of the policy, and the extent to which principals reported that their schools complied with the policy. Logistic regression models were generated for the parent and principal samples. Those parents reporting that their children's diets were healthier were more likely to agree that the policy reflected their beliefs and their children's dietary needs and preferences, that their child talked about the traffic light food classification system and that this system influenced their food choices in the supermarket. Those principals reporting full compliance with the policy were more likely to agree that implementing the policy was not overly difficult. Specific factors facilitating school compliance were canteen manager training and conducive kitchen setup. Provision of appropriate information and training prior to implementation may assist schools in implementing new food policies, thereby enhancing their impact beyond the school environment.